Functional interaction between charged nanoparticles and cardiac tissue: a new paradigm for cardiac arrhythmia? - Miragoli, Michele (Nanomedicine (Lond), 2012)
AIM: To investigate the effect of surface charge of therapeutic nanoparticles on sarcolemmal ionic homeostasis and the initiation of arrhythmias. MATERIALS & METHODS: Cultured neonatal rat myocytes were exposed to 50 nm-charged polystyrene latex nanoparticles and examined using a combination of hopping probe scanning ion conductance microscopy, optical recording of action potential characteristics and patch clamp. RESULTS: Positively charged, amine-modified polystyrene latex nanoparticles showed cytotoxic effects and induced large-scale damage to cardiomyocyte membranes leading to calcium alternans and cell death. By contrast, negatively charged, carboxyl-modified polystyrene latex nanoparticles (NegNPs) were not overtly cytotoxic but triggered formation of 50–250-nm nanopores in the membrane. Cells exposed to NegNPs revealed pro-arrhythmic events, such as delayed afterdepolarizations, reduction in conduction velocity and pathological increment of action potential duration together with an increase in ionic current throughout the membrane, carried by the nanopores. CONCLUSION: The utilization of charged nanoparticles is a novel concept for targeting cardiac excitability. However, this unique nanoscopic investigation reveals an altered electrophysiological substrate, which sensitized the heart cells towards arrhythmias.